2018
DOI: 10.1097/pcc.0000000000001388
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Cardiopulmonary Resuscitation in the Pediatric Cardiac Population: In Search of a Standard of Care*

Abstract: Objectives: Although clinical and pharmacologic guidelines exist for the practice of cardiopulmonary resuscitation in children (Pediatric Advanced Life Support), the practice of extracorpo-real cardiopulmonary resuscitation in pediatric cardiac patients remains without universally accepted standards. We aim to explore variation in extracorporeal cardiopulmonary resuscitation procedures by surveying clinicians who care for this high-risk patient population. Design: A 28-item cross-sectional survey was distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 45 publications
2
33
0
Order By: Relevance
“…In our institution and in other similar organizations with established extracorporeal life support (ECLS) programs, there is sufficient data to support the benefit of ECPR in children with cardiac disease who have an in-hospital cardiac arrest (see below) ( 3 , 11 , 13 , 16 , 26 31 ).…”
Section: Patient Selectionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our institution and in other similar organizations with established extracorporeal life support (ECLS) programs, there is sufficient data to support the benefit of ECPR in children with cardiac disease who have an in-hospital cardiac arrest (see below) ( 3 , 11 , 13 , 16 , 26 31 ).…”
Section: Patient Selectionmentioning
confidence: 98%
“…However, it is important these functional considerations are discussed and appreciated before and during resuscitation, and these place even more pressure on ensuring the system for ECPR is optimal for the performance of each of the phases of ECPR described below. There is variability in practice between institutions that use ECPR for pediatric patients with heart disease; there is a huge opportunity to gain knew insights on what protocols and interventions ensure the optimal quality of extracorporeal cerebral-CPR ( 11 ).…”
Section: Patient Selectionmentioning
confidence: 99%
“…Several studies have shown that survival with conventional CPR lasting >30 minutes ranges between 0% and 15%. [1][2][3][4][5][6] Extracorporeal cardiopulmonary resuscitation (ECPR) is the practice of rapid deployment of extracorporeal membrane oxygenation (ECMO) in patients having refractory cardiac arrest that is unresponsive to conventional CPR measures. Advantages of ECPR include early restoration of stable hemodynamics and adequate systemic output and consequently preservation of endorgan function and prevention of permanent injury.…”
Section: Introductionmentioning
confidence: 99%
“…In our analysis, epinephrine was often administered with a longer dosing interval than the 3-5 minutes recommended by the AHA (44). Decreased use of epinephrine during ECPR has been reported by some clinicians in attempt to avoid excessive afterload that may affect ECMO flow rates (45).…”
Section: Discussionmentioning
confidence: 93%